ASUPAN ZAT GIZI MAKRO DAN SERAT MENURUT STATUS GIZI ANAK USIA 6-12 TAHUN DI PULAU SULAWESI - Agustina, Wulan; Jus’at, Idrus; Mulyani, Erry Yudhya; Kuswari, Mury (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe aimed of this study was to determine the differences intake of macro-nutrients (protein, fat, carbohydrates) and fiber with respect to their nutritional status of children aged 6-12 years. This study was used secondary data Riskesdas 2010. The number of subjects was 2,987 children aged 6-12 years in Sulawesi Island. Body Mass Index for Age (BMI/U) was used to measure the nutritional status. Independent sample t-test and analysis of variance were applied to answer the research questions. The result showed that most of subjects were male (58.7%), living in rural areas (50.2%), and with low economic status (54.1%). In regard to protein intake, most of the children age 6 years was about 80-99% Recommended Dietary Intake (RDA). On the contrary, most of children 7-9 years and 10-12 years were below 70% RDA. There were no differences intake of macro-nutrients (protein, fat, carbohydrates) and fiber to the nutritional status of children aged 6-12 years (p>0.05). This study found that most of the children were suffering macro-nutrients intake regardless their nutritional status. Therefore, we need to have a good program to monitor nutritional status of school children.Keywords: nutrient intake, nutritional status, school age children 6-12 yearABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan asupan zat gizi makro (protein, lemak, karbohidrat) dan serat terhadap status gizi pada anak usia 6-12 tahun. Penelitian ini menggunakan data sekunder Riskesdas 2010 dengan pendekatan cross-sectional. Subjek penelitian adalah anak usia 6-12 tahun dengan status gizi kurus, normal, dan gemuk menurut IMT/U di Pulau Sulawesi tahun 2010 berjumlah 2.087 orang. Pengujian statistik menggunakan independent sample t-test dan Anova. Sebagian besar subjek berjenis kelamin laki-laki (58,7%), tinggal di perdesaan (50,2%), dan berstatus ekonomi rendah (54,1%). Rata-rata asupan protein pada kelompok umur 6 tahun termasuk kategori sedang (80-99% AKG) namun pada usia 7-9 tahun dan usia 10-12 tahun termasuk kategori defisit (<70% AKG). Tidak terdapat perbedaan asupan zat gizi makro dan serat terhadap status gizi (IMT/U) di Pulau Sulawesi (p>0,05). Penelitian ini menemukan adanya keberagaman asupan dan status gizi anak usia sekolah. Oleh karenanya, diperlukan program pemantauan status gizi secara rutin di sekolah.Kata kunci: anak usia 6-12 tahun, asupan zat gizi, status gizi